Derivatives theory and practice: An emerging markets perspective - Parameswaran, Sunil Kumar (Berlin Walter de Gruyter, 2024)
Though financial derivatives have been taught in courses in leading business schools for over 50 years, they are now universal, with exchanges having been set up around the globe. Excellent textbooks on derivatives are available. But many students in emerging markets desire a cogent and logical exposition that makes them aware of the specific challenges faced by their countries while developing exchanges.